Failure thresholds and weak part identification in cascade reservoir system: A risk-based optimization framework - Haibin Wang; Jiahong Liu; Chao Mei; Jia Wang; Tianxu Song (Journal of Hydrology: Regional Studies)
Study region: The upper Yalong River Basin(UYRB) Study focus: Extreme floods pose a huge threat to a cascade reservoir system. To minimize the impacts associated with cascade reservoir systems, this study proposes an optimized scheduling framework to identify weak points and failure thresholds for cascade reservoir system. Firstly, a Long Short-Term Memory (LSTM) model simulates flood evolution between reservoirs. Secondly, a dynamic Particle Swarm Optimization-Genetic Algorithm (PSO-GA) model optimizes outflow strategies during flood events. Thirdly, a quantitative assessment determined the cascade reservoir system's weak points and the failure thresholds. New hydrological insights for the region: Results show that failures result from either exceeding downstream storage capacity (EDSC) or exceeding the reservoir’s own capacity (EROC). The Le’an Reservoir in UYRB is identified as the system’s weak point. Under the optimized scenario, EDSC failures reduce flood resistance by 7.05 %–24.95 %, while EROC failures have minimal impact (0 %–1.62 %). Downstream storage capacity significantly influences system safety, and the weak point’s low failure threshold affects upstream reservoir scheduling through hydrodynamic interactions. Focusing on these critical risks can improve the resilience of cascade reservoir systems against extreme floods and increase the efficiency of flood control. Additionally, managers can develop emergency plans in advance based on the system’s weak points to ensure the safety of downstream cities.